Combining fiber dissection, plastination, and tractography for neuroanatomical education: Revealing the cerebellar nuclei and their white matter connections. Issue 1 (9th July 2013) - Arnts, Hisse; Kleinnijenhuis, Michiel; Kooloos, Jan G.M.; Schepens‐Franke, Annelieke N.; van Cappellen van Walsum, Anne‐Marie
<x xml:space="preserve">Abstract</x> In recent years, there has been a growing interest in white matter anatomy of the human brain. With advances in brain imaging techniques, the significance of white matter integrity for brain function has been demonstrated in various neurological and psychiatric disorders. As the demand for interpretation of clinical and imaging data on white matter increases, the needs for white matter anatomy education are changing. Because cross‐sectional images and formalin‐fixed brain specimens are often insufficient in visualizing the complexity of three‐dimensional (3D) white matter anatomy, obtaining a comprehensible conception of fiber tract morphology can be difficult. Fiber dissection is a technique that allows isolation of whole fiber pathways, revealing 3D structural and functional relationships of white matter in the human brain. In this study, we describe the use of fiber dissection in combination with plastination to obtain durable and easy to use 3D white matter specimens that do not require special care or conditions. The specimens can be used as a tool in teaching white matter anatomy and structural connectivity. We included four human brains and show a series of white matter specimens of both cerebrum and cerebellum focusing on the cerebellar nuclei and associated white matter tracts, as these are especially difficult to visualize in two‐dimensional specimens and demonstrate preservation of detailed human anatomy. Finally, we describe how the integration of white matter specimens with radiological information of new brain imaging techniques such as diffusion tensor imaging tractography can be used in teaching modern neuroanatomy with emphasis on structural connectivity. Anat Sci Educ. 7: 47–55. © 2013 American Association of Anatomists.